INCURABLE DISEASES - Mullajanova Gulnigor Ilhom kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Modern medicine has done a lot to eradicate and cure diseases, but unfortunately, there are still many horrific diseases for which there is no cure. 1. Ebola hemorrhagic fever. Ebola is a virus of the filovirus family that causes severe and often fatal viral hemorrhagic fever. Outbreaks of this disease have been observed in primates such as gorillas and chimpanzees and in humans. The disease is characterized by high fever, rash, and excessive bleeding. In humans, the fatality rate is 50 to 90 percent. The name of the virus comes from the Ebola River in the northern Congo Basin of central Africa, where it first appeared in 1976. That year, outbreaks in Zaire and Sudan led to hundreds of deaths. The Ebola virus is closely related to the Marburg virus, which was discovered in 1967, and both viruses are the only filoviruses that cause epidemics in humans.